Seaweed House Interior Design in Promoting a Contemporary Habitat and Promoting Tourism in Yandunjiao Village in Rongcheng City (Shandong Region, China) - Zho, Chengcheng; Noraziah Mohammad; Nor Haslina Ja`afar (Penerbit Universiti Kebangsaan Malaysia, 2023)
In the process of developing cities and regions, traditional Chinese architecture has been destroyed to a certain extent and the existing traditional architecture has become particularly precious. There is a contradiction within the modernization development phases and the protection of traditional architecture. To find a sustainable development way for the traditional villages is a problem that needs to be considered. The purpose of this study is to investigate how to preserve and redesign traditional architecture such as Seaweed House to adapt them to contemporary life and to promote tourism and economy of the region. The methods of fieldwork, participant observation and interview were used in the study. The findings indicated that the local residents have no initiative for the protection of traditional buildings. There are also certain deficiencies in the building, including a lack of space for modern equipment and leisure spaces in the Seaweed House. There is a lack of privacy in these dwellings due to the wooden structure and poor sound insulation between the rooms. The owner of the house used new and inappropriate materials when they renovated their house in recent years, resulting in a chaotic style and aesthetic. Some solutions are provided for these issues throughout this research study. It was also found that many traditional buildings have a lot of common problems in the process of protection and development. Once these problems are solved, the protection and development of traditional Chinese architecture will have progress.